2002
DOI: 10.1200/jco.2002.06.060
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of High-Risk Neuroblastoma With Triple-Tandem High-Dose Therapy and Stem-Cell Rescue: Results of the Chicago Pilot II Study

Abstract: The results of this pilot study demonstrate that it is feasible to intensify consolidation with triple-tandem high-dose chemotherapy and peripheral-blood stem-cell rescue and local irradiation, and suggest that this treatment strategy may lead to improved survival for patients with high-risk neuroblastoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
98
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(102 citation statements)
references
References 28 publications
1
98
0
3
Order By: Relevance
“…Therefore, the duration of induction chemotherapy was longer in the present study than those in other studies concerning HDCT/auto-SCT for high-risk NB. [2][3][4][5][6] In addition, two different and relatively intensive regimens (CEDC and ICE) were alternated during induction treatment in order to overcome possible drug resistance and to reduce drug toxicities. As a result, the response rate to induction was better in the present study than in other cooperative protocols.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the duration of induction chemotherapy was longer in the present study than those in other studies concerning HDCT/auto-SCT for high-risk NB. [2][3][4][5][6] In addition, two different and relatively intensive regimens (CEDC and ICE) were alternated during induction treatment in order to overcome possible drug resistance and to reduce drug toxicities. As a result, the response rate to induction was better in the present study than in other cooperative protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor status before the first HDCT/auto-SCT was CR for 24 patients, VGPR for 13, PR for 11 and MR for 1. A median of 4.7 Â 10 6 CD34 þ cells/kg (range, 1.4-38.9) was collected during the first leukapheresis round with a median of five leukapheresis events (range, [3][4][5][6][7][8][9][10][11]. One patient underwent a second leukapheresis round to collect at least 2 Â 10 6 CD34 þ cells/kg.…”
Section: Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sung et al 8,9 reported improved long-term survival using tandem HDCT/ASCR in patients with advanced neuroblastoma and high-risk brain tumors. Kletzel et al 10 also reported improved survival in a single-arm trial of triple-tandem HDCT/ASCR in patients with high-risk neuroblastoma. They demonstrated that further dose escalation using sequential HDCT/ASCR might result in additional improvements in the survival of patients with high-risk tumors.…”
Section: Introductionmentioning
confidence: 95%
“…[7][8][9][10] This treatment strategy is based on the hypothesis that a dose escalation might improve the survival of children with high-risk solid tumors. Recently, investigators have examined the efficacy of double or tripletandem HDCT/ASCR for further improvements in the outcome of patients with high-risk solid tumors.…”
Section: Introductionmentioning
confidence: 99%